The Athletic Spine - Mitchell, Tim; Burnett, A.; O'Sullivan, P. (Routledge, 2016)
In this ground-breaking new book, leading sports injury and rehabilitation professionals, strength and conditioning coaches, biomechanists and sport scientists show how this integrated model works across the spectrum of athlete care.